Satisfaction of Basic Psychological Needs Leads to Better Academic Performance via Increased Psychological Capital: A Three-Wave Longitudinal Study Among High School Students - Carmona-Halty, Marcos; Schaufeli, Wilmar B.; Llorens, Susana; Salanova, Marisa (Frontiers in Psychology, 2019)
This brief report proposes a model in which academic psychological capital (PsyCap) mediates between the satisfaction of student’s basic psychological needs and their academic performance, as assessed by students’ GPA. Participants were 407 adolescents, aged 12–18, recruited from three Chilean schools. Through structural equation modeling, direct and indirect effects were calculated. Results show that academic PsyCap (assessed at time 2) fully mediates the relationship between the satisfaction of basic psychological needs (assessed at time 1) and academic performance (assessed at time 3). This means that students whose basic psychological needs are satisfied at school experience more hope, efficacy, resilience, and optimism (PsyCap), which, in turn, leads to better academic performance. Both theoretical and practical implications of the results are addressed, as well as strengths and weaknesses and directions for future research.